Los deportes y la idea olímpica en la literatura polaca - Krupka, Pawel (Eslavística Complutense, 2003)
The presence of physical culture has been developed in a particular dimension in the Polish literature. Vauious manifestations of sports and competitions as well as sport ethics and, flrst of alí, of the Olympíc Idea and the Games as such, can be found in numerous Polish works ofXX century and also earlier. This article is a brief review of most signiflcant examples of those elements in Polish poetry, fiction and critics.